"We need more clips about Putin, and lots of them:" Russia's state-commissioned online visual culture. Issue 2 (4th March 2017) - Fedor, Julie; Fredheim, Rolf
Abstract : In this article, we examine how the Putin government is attempting to respond and adapt to the YouTube phenomenon and the vibrant oppositional online visual culture on Runet. We show how these processes are giving rise to new forms of state propaganda, shaped and driven above all by the quest for high-ranking search-engine results and the concomitant desire to appeal to the perceived new sensibilities of the Internet generation through the commissioning and production of "viral videos." We focus in particular on the videos created by Iurii Degtiarev, a pioneer in the development of this genre, whose works we explore in light of the "Kremlingate" email leaks, which offer inside information on the strategies and aims being pursued on the online visual front of the campaign to manage the Russian mediascape, and Degtiarev's own reflections on this subject. Examining the output of young creatives patronized by the Kremlin offers a "bottom-up" view to supplement studies of the Russian ideological and media landscape as shaped by "political technologists" such as Vladislav Surkov and Gleb Pavlovskii.